Appendiceal Perforation and Abdominal Wall Infection Caused by Invasive Mucormycosis in a Child with Acute Leukemia - Li C; Luo Y; Wang Y; Bai Q (Infection and Drug Resistance)
Chuanxin Li,1,* Yonghan Luo,2,3,* Yanchun Wang,2 Qiang Bai1 1Department of General Surgery, Kunming Children’s Hospital, Yunnan, People’s Republic of China; 2Second Department of Infectious Diseases, Kunming Children’s Hospital, Yunnan, People’s Republic of China; 3School of Life Sciences and Technology, Kunming University of Science and Technology, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Bai, Department of Pediatric Surgery, Kunming Children’s Hospital, Kunming, Yunnan, People’s Republic of China, 650000, Email bqetyy@163.comAbstract: Gastrointestinal mucormycosis is one of the most difficult forms of the disease to diagnose due to its lack of specific clinical features. It is extremely rare to observe gastrointestinal mucormycosis in pediatric acute leukemia patients undergoing chemotherapy. In this report, we describe a case of a child with acute leukemia who developed invasive mucormycosis, leading to appendiceal perforation and abdominal wall infection. Initially, surgical intervention was delayed due to concerns over exacerbating bone marrow suppression, which ultimately resulted in the progression of the intra-abdominal infection. However, after thorough debridement of the abdominal wall infection and treatment with liposomal amphotericin B, the patient gradually recovered. This case highlights the importance of early and complete debridement of abdominal wall infections and intra-abdominal abscesses to prevent the further spread of mucormycosis, shorten the course of the disease, and improve outcomes.Keywords: appendiceal perforation, abdominal wall infection, invasive mucormycosis, children, acute leukemia